Data analysis and interpretation : a handbook for postgraduate social scientists - Rasli, Amran (Penerbit UTM, 2006)
This book is designed to assist postgraduate social science students and researchers to complete their thesis, dissertation or research projects. This book is equipped with a CD-ROM containing data from a Ph.D thesis. The data will be used from start till end, so that the reader could see the continuous application of various statistical tools and techniques to address the research questions identified. Emphasis is given to various SPSS procedures and selected qualitative techniques. Methods for conducting validity and reliability tests as well as subsequent descriptive and inferential analyses are presented in a logical manner. Finally, methods for interpreting and discussing the research findings are presented accordingly.